Warrior [videorecording (DVD)] - O'Connor, Gavin; Hardy, Tom, 1977-; Edgerton, Joel, 1974-; Nolte, Nick; Morrison, Jennifer, 1979- (Lions Gate Home Entertainment, 2011)
An ex-Marine haunted by a tragic past, Tommy Riordan returns to his hometown of Pittsburgh and enlists his father, to train him for an MMA tournament awarding the biggest purse in the history of the sport. As Tommy blazes a violent path towards the title prize, his brother, Brendan, returns to the amateur ring to provide for his family. The two brothers must finally confront the forces that tore them apart, all the while waging the most intense, winner-takes-all battle of their lives.